1992
DOI: 10.2169/internalmedicine.31.1343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interferon(IFN) on Refractory Idiopathic Thrombocytopenic Purpura: Administration of 6 Million Units of Recombinant IFN alpha-2b.

Abstract: Five patients (six courses) with refractory idiopathic thrombocytopenic purpura (ITP) were given 6 million units of recombinant interferon (IFN) alpha-2b in 12 doses to achieve an improved response rate compared to previous studies using 3 million units. From the initial IFN administration, the platelet count increased from a pre-treatment level of 20.7 ± 17.7 X 103/ul (mean ± SD) and reached its first peak in weeks 2 or 3 of therapy (p<0.05). In week 5, the platelet count made its second and maximum peak (66.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…Increased platelet response was transient in the five patients displaying improvement. 10 Dubbeld et al treated 21 patients with refractory ITP and concluded results similar to the case reports previously discussed. Two patients showed complete response after 4 weeks of therapy that lasted up to 7 months and subsequently resulted in relapse.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Increased platelet response was transient in the five patients displaying improvement. 10 Dubbeld et al treated 21 patients with refractory ITP and concluded results similar to the case reports previously discussed. Two patients showed complete response after 4 weeks of therapy that lasted up to 7 months and subsequently resulted in relapse.…”
Section: Discussionsupporting
confidence: 70%
“…Two patients improved, one patient experienced slight improvement, and one patient became worse. Increased platelet response was transient in the five patients displaying improvement 10 …”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Eight studies investigated interferon alpha (22–29), and these included 83 patients (mean age 54 years, female 59%) were included. Three million units were administered subcutaneously 3 times weekly during 4 to 12 weeks except in 2 studies [ 24 , 26 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%